Preliminary Design Of Linear Low Density Polyethylene (LLDPE) Using Unipol Process Capacity Of 400,000 Tons/Year - Hasan, Achmad Amiruddin; , Tri Widayatno,S.T., MS.c., Ph.D; , ir. H. Haryanto, AR. MS (2015)
Linear Low Density Polyethylene (LLDPE) factory with a capacity of 400,000 tons/year is planned to operate for 330 days per year. The manufacturing process of LLDPE utilise solid catalyst TiCl4-MgCl2. The reaction takes place in a fluidized bed reactor in the gas-solid phase. It is exothermic, adiabatic and non-isothermal at inlet and outlet temperature of 75C and 80C and pressure of 25 atm. Products exit the reactor in the form of a solid resin with a conversion per pass of 5%. Factory is classified as a high risk due to plant operating conditions with high pressure. Polymerization formation reaction of LLDPE of ethylene takes place through three stages, namely the initiation stage in which the reaction occurs between ethylene gas with free radicals from the activation of the catalyst with a co-catalyst. The second stage is the propagation reaction and the last is the termination stage. Raw material of ethylene required for the plant is 50,596.785kg per hour, butene-1 is 3.400 kg per hour, hydrogen is 0.8162 kg per hour, catalyst TiCl4-MgCl2 as much as 2.5252 kg per hour and co-catalyst TEAL (Al(C2H5)3) totals is 37.9959 kg per hour. The products of LLDPE is 50505.0505 kg per hour. Supporting utilities include water supply of 367,003.12 kg per hour were obtained from Grogol river water, the provision is 5,255.325 kg per hour of saturated steam were obtained from the fuel boiler with fuel oil amounted to 621.371 liters per hour, the need for compressed air of 100 m3 per hour, the demand for electricity is obtained from the PLN and a generator set of 500 kW in reserve. The factory was established in Cilegon, Banten with a land area of 15,779 m2 and the number of employees 202 people. LLDPE factory requires a fixed capital of IDR 598,874,667,292 and working capital of IDR 478,453,884,401. The economic analysis of this plant show a profit before tax of IDR 429,859,745,392 per year after taxes 30%, The profit reached IDR 300,901,828,074 per year. Percent Return On Investment (ROI) before tax and after tax are 71.81% and 50.27%. Respectably Pay Out Time (POT) before tax and after tax for 5 years are 1.25 and 1.72. Respectably Break Even Point (BEP) is 49.35%, and Shut Down Point (SDP) amounted to 41.34%. Discounted Cash Flow (DCF) accounted for 31.01%. From the above data of feasibility analysis, it can be concluded that the plant is profitable and feasible to be established.